2023
DOI: 10.3389/fspas.2023.1118758
|View full text |Cite
|
Sign up to set email alerts
|

The evolving paradigm of the subauroral geospace

Abstract: An assessment of the status quo of fast subauroral flows—subauroral ion drifts (SAID) and subauroral polarization streams (SAPS), is presented. For a few decades, their development has been interpreted in terms of the voltage and current magnetospheric generators based largely on the drift motion of test particles. Recent multispacecraft observations revealed serious flaws in the generator paradigm and called for a new generation mechanism of fast-time subauroral flows and ring current (RC) injections. A novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 84 publications
1
16
0
Order By: Relevance
“…Demonstrated with 6 SAID events and by invoking the short-circuiting theory of fast-time SAID development (Mishin, 2013(Mishin, , 2023Mishin & Puhl-Quinn, 2007), we have explained the close relation of the newly-formed outward SAID E field (based on its plasma environment still showing the signatures of short-circuiting) and the newly-formed plasmapause observed by VAP in the inner magnetosphere. But this close relation also includes the activations of lower-hybrid and upper-hybrid plasma waves, modeled by Mishin and Burke (2005) and shown in their Figure 13, leading to the hot zone's development (Mishin & Streltsov, 2021a).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Demonstrated with 6 SAID events and by invoking the short-circuiting theory of fast-time SAID development (Mishin, 2013(Mishin, , 2023Mishin & Puhl-Quinn, 2007), we have explained the close relation of the newly-formed outward SAID E field (based on its plasma environment still showing the signatures of short-circuiting) and the newly-formed plasmapause observed by VAP in the inner magnetosphere. But this close relation also includes the activations of lower-hybrid and upper-hybrid plasma waves, modeled by Mishin and Burke (2005) and shown in their Figure 13, leading to the hot zone's development (Mishin & Streltsov, 2021a).…”
Section: Discussionmentioning
confidence: 72%
“…As shown in Figure 5 and Figure S16 in Supporting Information S1, this SAID event's most apparent characteristics are the large increase of the AU index (from 87 to 1,007 nT) and the narrow extent of the overlapping hot-zone-heat-source developed across the plasmapause and at the tailward edge of the plasmasphere, and in the regime of maximum temperature anisotropy. These imply that during the SAR arc event, plasmaspheric heating was generated by both (a) the energetic electrons coming from the TPBL (Mishin, 2013(Mishin, , 2023Mishin & Sotnikov, 2017) and (b) the low-frequency (including EMIC) waves developed in the coinciding heat-source-hot-zone region situated in the regime of TPBL. The following downward transports (along the magnetic field lines) of heat and energetic electron fluxes (enhanced by the TPBL, Mishin & Streltsov, 2021a) and collisions with precipitating low-energy electrons (Mishin et al, 2004) led to the elevated ionospheric Te (∼6,000 K observed by F15) and SAR arc development (as Te > Te min required for 630 nm red-line emission; Kozyra et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Based on a few M-I conjugate observations, the inward (earthward) ASAID E field (observed by TH-A and VAP-B) could be studied by invoking novel generation theories. These include (a) the short-circuiting theory put forward for fast-time SAID development based on observational evidence (Mishin, 2013(Mishin, , 2023Mishin & Puhl-Quinn, 2007) that we applied to the fast-time development of ASAID, and (b) the finite Larmor radius effects (Voiculescu & Roth, 2008) along with (c) the hot-ring-current-cold-plasmasphere interface (Voiculescu, 2012) put forward for ASAID development based only on theoretical considerations that we explained with the behavior of magnetized hot ions and demonstrated with satellite observations, and thus verified with observational evidence in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al, 2021). SAID are created as an integral part of the VG FT by the short circuiting of earthbound MPFs over the plasmapause (Mishin, 2013(Mishin, , 2023. As a result, SAID appear in the near midnight plasmasphere interior to L min -the L-shell where the plasma density at the plasmapause exceeds the critical value of 𝐴𝐴 𝐴𝐴p(𝐿𝐿min) = 𝐴𝐴 (min) p ∼ 10 cm −3 .…”
Section: Substorm Said: Implications For Subauroral Arcsmentioning
confidence: 99%